The Impact of Self-Massage Method on The Elderly’s Sleep Quality - Oktafiranda, Nadya Dwi; Diyananda, Dzulfiqar; Yuliana, Ela; Ihsani, Sri Indah; Mulia, Lita (Universitas PGRI Palembang, 2025)
The purpose of this atudy is to ascertain how to the self-massage technique affect the quality of sleep in the elderly at the hanna nursing home, Bogor. The research method used in this study is the Pre-Experiment method. The research instrument in the form of The Puttsburgh Sleep Quality Index (PSQI) questionnaire was used to measure the quality of sleep of the elderly before and after performing self-massage. This research was conducted in May 2024 at Panti Werdha Hanna, Bogor. The sample in the study amounted to 14 elderly people who met the criteria. Sampling using purposive sampling technique. Based on the data from this study, it shows that the average value of sleep quality in the pre-test is 5.1 and the posttest results are lower with a value of 4.1. The results of the paired sample T test show that the significance value is 0.013 <0.05, which means that there is a significant difference between the value of the pretest results and the value of the posttest results. Based on the result, it can be said that the elderly residents of panti wredha hanna benefit greatly from the self-massage the receive